Mutagenic Effectiveness and Efficiency of Gamma Rays and Ethyl Methanesulphonate in Pea (Pisum sativum L.) - Pachkore3 and R. A. Satpute4, G. S. Dhulgande1*, D.A. Dhale2, G. L. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Mutagenic effectiveness is a measure of the frequency of mutations induced by unit dose of a mutagen while efficiency gives the proportion of mutations in relation to other associated undesirable biological effects such as lethality, pollen sterility and gross chromosomal aberrations induced by the mutagen (Konzak,et.al.,1965). The usefulness of any mutagen in plant breeding depends not only on its mutagenic effectiveness but also on its mutagenic efficiency. Studies on mutagenic effectiveness and mutagenic efficiency of physical mutagen (gamma rays) and chemical mutagen (EMS) on two varieties of pea, namely, DDR-53 and DMR-55 have been reported. The treatments included three doses of gamma rays (5kR, 7kR, and10kR) and three concentrations of EMS (0.05%, 0.10% and 0.15%).